Factors associated with the SMES preferences towards Islamic banking products and services - Ahmad, Kamilah; Othman, Khairunnisah; Zabri, Shafie Mohamed; Atan @ Yaakub, Anisah (American Scientific Publishers, 2018)
Islamic banking institution is one of the competitive players in the finance sector that provides a variety of banking product and services. However there is lack information regarding Islamic banking preferences among small and medium-sized enterprises. Thus, this paper aims to investigate the preferences of SMEs towards Islamic banking products and services and factors associated with their banking preferences. This study utilized a quantitative method and the data were collected using a questionnaire survey conducted among owner/managers of the Malaysian SMEs. Based on the 70 completed replies, the study reveals that the level of preferences of SMEs on Islamic banking products and services is moderate. Furthermore, the study shows that service quality, religion motivation, location convenience, knowledge, easy access to loans and size of an enterprise have significant correlations with Islamic banking products and services preferences. The findings contribute new information to the body of knowledge on factors associated with Islamic banking preferences among SMEs which will enable banks to reformulate strategies for increasing their future market share.